Molecular Rotational Correlation Times and Nanoviscosity Determined by 111mCd Perturbed Angular Correlation (PAC) of γ‐rays Spectroscopy. Issue 9 (29th December 2022) - Fromsejer, Rasmus; Jensen, Marianne L.; Zacate, Matthew O.; Karner, Victoria L.; Pecoraro, Vincent L.; Hemmingsen, Lars
Abstract: The nanoviscosity experienced by molecules in solution may be determined through measurement of the molecular rotational correlation time, τ c, for example, by fluorescence and NMR spectroscopy. With this work, we apply PAC spectroscopy to determine the rate of rotational diffusion, λ =1/ τ c, of a de novo designed protein, TRIL12AL16C, in solutions with viscosities, ξ, from 1.7 to 88 mPa⋅s. TRIL12AL16C was selected as molecular probe because it exhibits minimal effects due to intramolecular dynamics and static line broadening, allowing for exclusive elucidation of molecular rotational diffusion. Diffusion rates determined by PAC data agree well with literature data from fluorescence and NMR spectroscopy, and scales linearly with 1/ ξ in agreement with the Stokes–Einstein–Debye model. PAC experiments require only trace amounts (∼10 11 ) of probe nuclei and can be conducted over a broad range of sample temperatures and pressures. Moreover, most materials are relatively transparent to γ‐rays. Thus, PAC spectroscopy could find applications under circumstances where conventional techniques cannot be applied, spanning from the physics of liquids to in‐vivo biochemistry. Abstract : Brownian molecular tumbling rates in solution have been measured by using 111m Cd perturbed angular correlation of γ‐rays (PAC) spectroscopy and a de novo designed molecular probe (a trimeric coiled‐coil protein). Most materials are relatively transparent to γ‐rays, and PAC spectroscopy might find applications where conventional methods probing rotational correlation times, for example, NMR and fluorescence spectroscopy, cannot be applied—from the physics of liquids to in‐vivo biochemistry.